In vitro Regeneration of the Medicinal Plant, Plumbago zeylanica L. with Reference to a Unique Population in Maruthamalai, the Western Ghats, India - Mallikadevi, T.; Senthilkumar, P.; Paulsamy, S. (Plant Tissue Culture and Biotechnology, 2009)
The in vitro regeneration of Plubago zeylanica exhibited that the callus was initiated in the basal medium containing BAP, NAA, 2, 4-D, and IBA. The high amount (90%) of organic calli was induced in the basal medium supplemented with 2, 4-D, alone at 2.0 mg/l. In the subculture the adventitious shoot formation was prominently higher (83%) in the basal medium containing BAP, and NAA at 3.5 and 0.3 mg/l, respectively. IAA (1.0 mg/l)effectively produced higher percen-tage (90) of roots and root growth. After sequential hardening, survivability rate was observed to be significantly higher (80%) in the hardening medium containing garden soil, sand and vermicompost in the ratio of 1 : 1 : 1 by volume under greenhouse condition. Key words: Plumbago zeylanica, In vitro regeneration, Medicinal plant D.O.I. 10.3329/ptcb.v18i2.3648 Plant Tissue Cult. & Biotech. 18(2): 173-179, 2008 (December)